(untitled) (Journal of Science and Technology, 2016)
This paper examines the taboos that are associated with some traditional arts, namely woodcarving, cloth-weaving, iron-smithing and pottery as practiced among the rural folk in Ghana and their implications in the society. It outlines the drawbacks that these taboos exert on the opportunities for the young in the practice of those arts. Suggestions are offered to bolster efforts being made to overcome the drawbacks so that the young people could avail themselves of those opportunities formerly denied.